PROJECT RISK MANAGEMENT IN SECTOR PUBLIC (Lessons Learned from Indonesia) - Aisyah Almira; Nurkholis Nurkholis; Sari Atmini (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
This study examines the implementation of risk management in public sector infrastructure projects in Indonesia funded by the APBN. Using a qualitative approach and case study method, data were collected through in-depth interviews with stakeholders such as risk managers and risk management teams. The findings indicate that the main risks include land acquisition, design, contractual, and completion time risks. Although risk management is applied at every stage, the lack of documentation hampers the evaluation of its effectiveness. The guidelines provided by the Ministry of Public Works and Housing help accommodate the primary risks but require further adjustments. The urgency of implementing risk management is high to prevent delays and cost overruns. It is recommended to develop specific guidelines, enhance documentation, and conduct continuous training and active collaboration among stakeholders to improve risk management effectiveness and ensure the success of infrastructure projects.